Locating Globalization: Feminist (Re)readings of the Subjects and Spaces of Globalization - Nagar, Richa; Lawson, Victoria; McDowell, Linda; Hanson, Susan (Economic geography, 2002)
The literatures on economic globalization and feminist understandings of global processes have largely remained separate. In this article, our goal is to bring them into productive conversation so that research on globalization can benefit from feminist engagements with globalization. In the first section, which focuses on the conceptual challenges of bringing the economic globalization literature into conversation with feminist analysis, we identify several key exclusions in that literature and propose parallel inclusions that a feminist reading of globalization suggests. Our suggested inclusions relate to the spaces, scales, subjects, and forms of work that research on economic globalization has largely neglected. The second section takes up several key themes in the large body of feminist research on global economic processes, which is also largely absent from the economic globalization literature: the gendering of work, gender and structural adjustment programs, and mobility and diaspora. In the final section, we address the implications of feminist epistemologies and methodologies for research on economic globalization. Here we argue for grounded, collaborative studies that incorporate perspectives of the south as well as the north and that construct understandings of place and the local, as well as space and general global processes; we point to the coconstitution of different geographic scales and highlight the need for studies that cut across them. The article demonstrates how a feminist analysis of globalization entails far more than recognizing the importance of gender; it requires substantial rethinking of how to conceptualize, study, and act in relation to economic globalization.